Inkjet-printed internal light extraction layers for organic light emitting diodes. (9th February 2018) - Eiselt, Thomas; Preinfalk, Jan B; Bittkau, Karsten; Gomard, Guillaume; Hanemann, Thomas; Lemmer, Uli
Abstract: We have developed inkjet-printed scattering layers for enhanced light extraction in organic light emitting diodes (OLEDs). These layers are based on scattering polymer/nanoparticle composites, which are prepared from a solvent-free process and used for the outcoupling of waveguide modes to free propagating modes, thus improving the device efficiencies. Two different monomers are examined and an inkjet-printing process is developed for each of them. We first analyze the inks' rheological properties, followed by the optical and morphological properties of the resulting layers. Upon integration of these printed layers into an OLED stack, the device efficiencies are increased by up to 40% with respect to an unpatterned reference device. Furthermore, we show that these internal light extraction layers improve the angular and spectral stability of the devices.